2023
DOI: 10.3390/polym15102358
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Testing of Polymer Composites and Textile Cords for Tires

Abstract: This paper is oriented toward the specific testing of polymer composites and textile PA66 cords used as reinforcement for composites. The aim of the research is to validate the proposed new testing methods for low-cyclic testing of polymer composites and PA66 cords for the characterization of material parameters useful as input data for computational tire simulations. Part of the research is the design of experimental methods for polymer composites and test parameters such as load rate, preload, and other para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Experimental studies on the tensile behavior of aramid and polyamide cords are reported in [5]. Cyclic tests on nylon66 cords are described in detail in [6]. Test results on rayon greige and dipped cords are described later on in this work; they have recently been obtained within an experimental campaign that complements the one reported in [7,8].…”
Section: Introductionmentioning
confidence: 95%
“…Experimental studies on the tensile behavior of aramid and polyamide cords are reported in [5]. Cyclic tests on nylon66 cords are described in detail in [6]. Test results on rayon greige and dipped cords are described later on in this work; they have recently been obtained within an experimental campaign that complements the one reported in [7,8].…”
Section: Introductionmentioning
confidence: 95%